Fresno County Board of Supervisors Presenting Retirement Plaques to ? And Floyd Viau, Jr. - Watkins, Howard::::::::: (1985)
Fresno County Counsel Floyd Viau giving final words prior to formal retirement; Supervisor Betty Ramacher on far left